EXOTIC SPECIES OF SOCOTRA ISLAND, YEMEN: A FIRST CONTRIBUTION - SOMASHEKAR, R.K.; ATTORRE, F.; TALEB, N.; BRUNO, F. (Annali di Botanica, 2010)
A first inventory of the exotic species of Socotra has been compiled on the basis of the published literature and original distribution data collected by field surveys from 2006 to 2008. A strictly geographical and conservative approach was adopted including only cultivated species and those with a native range separated from Socotra territory. The extracted aliens (87 taxa, 68 genera, 40 family) represent approximately 9% of the total flora of the region (850 taxa). Most were introduced in the past 10 to 20 years. Agricultural cultivated or crop species dominated with 38 species (43.7%), fruit followed by basing 14 species (16.1%) and ruder or ornamental species (35 species, 40.2%).